2007
DOI: 10.1242/dev.003715
|View full text |Cite
|
Sign up to set email alerts
|

Ftm is a novel basal body protein of cilia involved in Shh signalling

Abstract: In this study we show in mice that Ftm (Rpgrip1l) is located at the ciliary basal body. Our data reveal that Ftm is necessary for developmental processes such as the establishment of left-right asymmetry and patterning of the neural tube and the limbs. The loss of Ftm affects the ratio of Gli3 activator to Gli3 repressor, suggesting an involvement of Ftm in Shh signalling. As Ftm is not essential for cilia assembly but for full Shh response, Ftm can be considered as a novel component for cilium-related Hh sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
242
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(261 citation statements)
references
References 54 publications
(85 reference statements)
16
242
1
2
Order By: Relevance
“…1B). This incidence of heterotaxia is quite similar to what has been previously observed in well-established LR mutants [for instance, KiF3B mutants (Nonaka et al, 1998), cilia-related mutants (Bonnafe et al, 2004;Vierkotten et al, 2007;Zhao and Malicki, 2007), and ablation of cells at the node (Essner et al, 2005)]. We conclude that organizers induced by XSiamois do not have the ability to correctly pattern the LR axis.…”
Section: Fig 1 Late Rescue Of Uv Irradiation Via Injection Of Licl Orsupporting
confidence: 87%
“…1B). This incidence of heterotaxia is quite similar to what has been previously observed in well-established LR mutants [for instance, KiF3B mutants (Nonaka et al, 1998), cilia-related mutants (Bonnafe et al, 2004;Vierkotten et al, 2007;Zhao and Malicki, 2007), and ablation of cells at the node (Essner et al, 2005)]. We conclude that organizers induced by XSiamois do not have the ability to correctly pattern the LR axis.…”
Section: Fig 1 Late Rescue Of Uv Irradiation Via Injection Of Licl Orsupporting
confidence: 87%
“…In contrast, no change was observed in non-ciliated areas, 22 suggesting that Ftm relies on cardiac primary cilia for signaling, and that the heart phenotypes in the Ftm −/− mouse are primary cilia-dependent. Ftm seems to be involved in the processing of Gli3, 161 and in agreement with this, the amount of unprocessed Gli3 is 10-fold higher in Ftm −/− hearts compared with heart of control littermates. 22 The cardiac phenotypes described above suggest that Hh signaling is important for proliferation and differentiation of cardiomyocytes and are thus in agreement with the previous findings that primary cilia in part coordinate Hh signaling during the differentiation of stem cells into cardiomyocytes.…”
Section: Cardiac Primary Cilia and Coordination Of Hedgehog Signalingsupporting
confidence: 77%
“…136,142 Septation of the ventricles is also dependent on the gene Fantom (Ftm) 22 that encodes the ciliary base protein Rpgrip1l/Nphp8, which is required for proper ciliogenesis, PCP, and Shh signaling, and when mutated leads to a series of ciliopathies. 22,[52][53][54][160][161][162][163][164][165] In Ftm null mouse embryos, 33% of all analyzed embryos had VSD in the membranous part of the septum, 81.5% had defects in the muscular part, and all analyzed embryos had reduced atrial and ventricular wall thickness. 22 In the ciliated areas of Ftm −/− embryonic hearts at E11.5, the rate of proliferation and Shh signaling was markedly reduced.…”
Section: Cardiac Primary Cilia and Coordination Of Hedgehog Signalingmentioning
confidence: 99%
“…In addition to being an important inductive signal in embryonic development, Hh signaling is required in homeostasis of mature tissues and is also implicated in many human cancers, including endodermal derived carcinomas of the esophagus, stomach, and pancreas (Beachy et al, 2004) as well as neurodegenerative disorders (Bak et al, 2003). Although the mechanism is not completely understood, it has been shown that Hh signaling is coordinated by the primary cilium (e.g., Huangfu et al, 2003;Corbit et al, 2005;Huangfu and Anderson, 2005;May et al, 2005;Haycraft et al, 2005;Liu et al, 2005a;Koyama et al, 2007;Vierkotten et al, 2007;Ruiz-Perez et al, 2007;Caspary et al, 2007;Rohatgi et al, 2007;Kiprilov et al, 2008). Regulation of the Hh pathway is complex with Hh responsive Gli transcription factors having either activator or repressor functions that depend on IFT proteins.…”
Section: Introductionmentioning
confidence: 99%